2019
DOI: 10.3390/genes10040265
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effects of LPIN1 Polymorphisms on Milk Production Traits in Dairy Cattle

Abstract: Our initial RNA sequencing work identified that lipin 1 (LPIN1) was differentially expressed during dry period, early lactation, and peak of lactation in dairy cows, and it was enriched into the fat metabolic Gene Ontology (GO) terms and pathways, thus we considered LPIN1 as the candidate gene for milk production traits. In this study, we detected the polymorphisms of LPIN1 and verified their genetic effects on milk yield and composition in a Chinese Holstein cow population. We found seven SNPs by re-sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
4
13
1
Order By: Relevance
“…On the other hand, missense mutation might be a candidate for production traits in cattle, there is a superior correlation between the gene polymorphisms and productive traits (26) , also, the missense mutations could be lead to a change in the protein structure (27) , this is consistent with the results of the study (Fig. 3), as the protein structure differed in all four haplotypes.…”
Section: Cont Table (2) Type Of Mutations In the Cyp19 Gene In Holstein Bulls In Iraqsupporting
confidence: 88%
“…On the other hand, missense mutation might be a candidate for production traits in cattle, there is a superior correlation between the gene polymorphisms and productive traits (26) , also, the missense mutations could be lead to a change in the protein structure (27) , this is consistent with the results of the study (Fig. 3), as the protein structure differed in all four haplotypes.…”
Section: Cont Table (2) Type Of Mutations In the Cyp19 Gene In Holstein Bulls In Iraqsupporting
confidence: 88%
“…A study has revealed that the use of available loci improved the accuracy of genomic prediction in dairy cattle [19], which suggests that loci that are associated with milk production traits could be used in genomic selection programs that are aimed at accelerating genetic progress of dairy cattle. Studies have shown that the SNPs in the candidate genes significantly influenced the milk yield and composition in Holsteins [20,21,22,23,24,25]. In this study, we identified ten SNPs in NUCB2 and found that the SNPs and haplotypes of this gene were significantly associated with milk production traits.…”
Section: Discussionmentioning
confidence: 68%
“…Genomic selection is widely used in dairy cattle breeding, and the development of efficient SNP markers can improve the accuracy of the selection. Studies have shown that the SNPs in the functional genes significantly influenced the milk production traits in dairy cattle [3740]. Thus, the SNPs with large genetic effects on milk traits could be used as markers to increase the selection efficiency in specific dairy cattle populations.…”
Section: Discussionmentioning
confidence: 99%